The Stronger Azerbaijani Diaspora in Foreign Policy of Azerbaijan - Mukhtarova, Nazmiyya; Ismayilova, Ulviyya; Ahmadova, Bayim (ADA University, 2023)
The role of diaspora communities in promoting the interests of their homeland abroad and shaping its foreign policy is vital. Having been an integral part of the international system, which encompasses the complex web of political, economic, social, and cultural interactions among states, it is also crucial for Azerbaijan to have an effective diaspora community that represents its interests abroad. This Capstone project aims at analyzing the challenges of strengthening the Azerbaijani diaspora. The project has revealed that the country’s diaspora community is fairly new and small. The study proposes policy options for each of these challenges encountered by the diaspora community of our homeland – organization of lobbying activities, establishment of financial funds, and unification of diaspora members. The proposed policy options are evaluated against the five main criteria: effectiveness, equity, feasibility, and flexibility. Along with the combination of primary and secondary data sources, semi-structured interviews with relevant experts have been conducted. The project reveals that in order to tackle the respective issues successfully, there should be a reliable financial mechanism and unification among the Azerbaijani diaspora communities.
Keywords: Diaspora -- Azerbaijan; Lobbying -- Azerbaijan; Community organization -- Azerbaijani diaspora; Public and International Affairs